Tracking the emergence of epitaxial metal–oxide interfaces from precursor alloys. Issue 45 (15th September 2021) - Wen, Yu; Abe, Hideki; Mitsuishi, Kazutaka; Hashimoto, Ayako
Abstract : The oxidation process of a Pt5 Ce alloy that leads to self-assembled Pt/CeO2 nanocomposites with an epitaxial heterointerface was elucidated by atomic-resolution transmission electron microscopy. Abstract : Heterointerfaces with an epitaxial relationship, self-assembled nanocomposites of Pt(111)/CeO2 (111) 60°, were successfully formed by simple oxidation of Pt5 Ce alloy. Oxygen dissolution into the alloy causes spacial periodic compositional perturbation by atomic segregation, specifically, by local diffusion of Pt and Ce atoms. A striped pattern of Pt and CeO2 with a 4–5 nm periodicity formed through phase transformation of the Pt-rich alloy and oxidation of the Ce-rich alloy, respectively. Notably, a fully epitaxial relationship between the Pt and CeO2 phases was observed even in the initial stage. With continued annealing, the crystals rotated into an energetically favorable orientation with respect to the remaining (111)Pt//(111)CeO2 . The alloy oxidation and its resulting nanoscale phase-separation behavior were verified in an ex situ annealing experiment of an alloy specimen, which had been first thinned by a focused ion beam. Changing the oxygen partial pressure to the reaction interface may alter the orientation relationship between the hexagonal close-packed Pt5 Ce structure and face-centered cubic Pt/CeO2 structure, thereby altering the growth direction of the separated phases. These findings present a pathway for the self-assembly of epitaxial Pt(111)/CeO2 (111) interface and are expected to assist the structural design of metal–oxide nanocomposites.